Analysis of Drivers and Barriers to Ecotourism Development - Kambu, Selviana; Rumerung, D.; Leasiwal, Teddy Ch. (Public Policy, 2024)
This study aims to integrate various aspects of ecotourism development and evaluate development strategies, specifically focusing on Lake Uter ecotourism. It employs descriptive methods with both qualitative and quantitative approaches. Data collection involved literature study, observation, interviews, and documentation, utilizing sources like books, journals, the internet, and other relevant documents. Data were analyzed using the Miles and Huberman model. The findings reveal that the driving factors for the development of Lake Uter ecotourism are its uniqueness, support from the Maybrat district government, and community backing. Conversely, the inhibiting factors include the local government's low prioritization of the tourism sector, limited tourism human resources, and the absence of investors in the development of Lake Uter Ecotourism.